2015
DOI: 10.1161/hypertensionaha.114.04850
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors After Early-Onset Preeclampsia, Late-Onset Preeclampsia, and Pregnancy-Induced Hypertension

Abstract: C ardiovascular disease (CVD) has gained interest in obstetrics in recent years because large observational studies revealed a remarkable increase in the long-term risk of CVD in women who experienced different types of gestational hypertensive disorders.1-3 These include pregnancy-induced hypertension (PIH) and preeclampsia, which affect 2% to 7% of all pregnancies worldwide. 4A review by Bellamy et al 1 showed an increase of the postpartum risk of CVD events according to the severity of the hypertensive preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(194 citation statements)
references
References 34 publications
10
172
2
1
Order By: Relevance
“…Three individual studies performed in Norway, California, and Taiwan indicated that women with preeclampsia have a #12-fold increase in risk for developing cardiovascular disease (73,82,83). Additional adverse outcomes, such as the increased risk of renal disease (84), metabolic disorders (85,86), and death (73), have also been reported. Early-onset preeclampsia conferred a higher risk of end organ damage in terms of cardiovascular, respiratory, central nervous, renal, and hepatic systems compared with late onset (87).…”
Section: Maternal Outcomesmentioning
confidence: 99%
“…Three individual studies performed in Norway, California, and Taiwan indicated that women with preeclampsia have a #12-fold increase in risk for developing cardiovascular disease (73,82,83). Additional adverse outcomes, such as the increased risk of renal disease (84), metabolic disorders (85,86), and death (73), have also been reported. Early-onset preeclampsia conferred a higher risk of end organ damage in terms of cardiovascular, respiratory, central nervous, renal, and hepatic systems compared with late onset (87).…”
Section: Maternal Outcomesmentioning
confidence: 99%
“…Progression to chronic hypertension postpartum may help further elucidate whether GH and preeclampsia have distinct etiologies. Specifically, 42% of women with preeclampsia and 39% of women with GH progress to hypertension after mean follow‐up of 2.5 years compared with rates as low as 1% among women with normotensive pregnancies 20, 21…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…[22][23][24][25][26][27] An overview of studies on established and novel CVD risk factors in women with a history of preeclampsia, including anthropometric measures, circulating markers and imaging modalities, is presented in Table 2. In a recent meta-analysis by Hermes et al several traditional risk factors for CVD (glucose, insulin, triglycerides, total cholesterol, HDL-cholesterol, low-density lipoprotein (LDL) cholesterol and homocysteine levels) were confirmed to be associated with previous preeclampsia in comparison to same-age women with a history of an uncomplicated pregnancy.…”
Section: Major and Contributing Cvd Risk Factorsmentioning
confidence: 99%